Measurement of ϒ production in pp collisions at [Formula: see text]. - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; et al. (2012)
The production of ϒ(1S), ϒ(2S) and ϒ(3S) mesons in proton-proton collisions at the centre-of-mass energy of [Formula: see text] is studied with the LHCb detector. The analysis is based on a data sample of 25 pb(-1) collected at the Large Hadron Collider. The ϒ mesons are reconstructed in the decay mode ϒ→μ (+) μ (-) and the signal yields are extracted from a fit to the μ (+) μ (-) invariant mass distributions. The differential production cross-sections times dimuon branching fractions are measured as a function of the ϒ transverse momentum p T and rapidity y, over the range p T <15 GeV/c and 2.0